Uji Performa Mesin Penggali Tanahmenggunakan Motor Tipe Sg 200 Untuk Pengolahan Lahan Gambut - Firman Alhaffis, Khairil Anwar (Techno Bahari, 2019)
Soil digging machines are devices equipped with digging blades to be used for digging. The earth digging machine aims to make commensurate excavation or land processing in the agricultural field, the use of the machine is faster when compared to the manual method that still uses human power and the work of the land is done a lot by the local community, especially in peat soil areas. From the process of making the equipment that is first done is to choose the material needed to make the device according to the design, while the components used are 7.0 Hp drive motor, gearbox, plate, elbow iron, steel shaft, then the thing to do is manufacture the engine frame, the application of the blade, and the final stage of assembly of the tool. The results of the excavation process in the range of 0-5 meters using a machine takes 273,8 seconds, for testing the manual method of hoes and machetes ranging from 0-5 meters takes 368 seconds, both diggers have a width of 38 cm and are able to dig to a depth of 10 cm-15 cm.